2013
DOI: 10.1002/wrna.1183
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of genes in the arachidonic acid metabolic pathway by RNA processing and RNA‐mediated mechanisms

Abstract: Arachidonic acid (AA) is converted by enzymes in an important metabolic pathway to produce molecules known collectively as eicosanoids, 20 carbon molecules with significant physiological and pathological functions in the human body. Cyclooxygenase (COX) enzymes work in one arm of the pathway to produce prostaglandins (PGs) and thromboxanes (TXs), while the actions of 5-lipoxygenase (ALOX5 or 5LO) and its associated protein (ALOX5AP or FLAP) work in the other arm of the metabolic pathway to produce leukotrienes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 126 publications
(172 reference statements)
0
14
0
Order By: Relevance
“…and ). The results indicate that 5‐LO activity is reduced following fracture, perhaps by signaling initiated by one or more of the rapidly‐induced inflammatory cytokines or through a coordinated gene expression regulatory mechanism . The results also suggest that 5‐LO and associated lipid mediators may function to mitigate the inflammatory response, serving perhaps as anti‐inflammatory mediators or as pro‐resolving mediators .…”
Section: Discussionmentioning
confidence: 88%
“…and ). The results indicate that 5‐LO activity is reduced following fracture, perhaps by signaling initiated by one or more of the rapidly‐induced inflammatory cytokines or through a coordinated gene expression regulatory mechanism . The results also suggest that 5‐LO and associated lipid mediators may function to mitigate the inflammatory response, serving perhaps as anti‐inflammatory mediators or as pro‐resolving mediators .…”
Section: Discussionmentioning
confidence: 88%
“…Multiple forms of post-transcriptional regulation may be at play resulting in this disparity between FLAP mRNA and protein expression. There are two predicted splice variants of FLAP, both of which have the same 322 bp 3′ UTR (Figure 3A and [ 2 ]). Expression of the protein isoform of the second splice variant has yet to be experimentally validated.…”
Section: Resultsmentioning
confidence: 99%
“…COX-1 and COX-2 perform the same two enzymatic activities: oxidative cyclization and peroxidation of AA (2 and references therein). Our lab and others have demonstrated that COX-2 expression is regulated both transcriptionally and post-transcriptionally, including regulation by alternative polyadenylation of the COX-2 3′ untranslated region (3′ UTR) [ 16 , 17 ] and microRNA (miRNA)-mediated regulation by several different miRNAs in multiple cell types and tissues [ 2 , 18 , 19 ]. Most notable for the purposes of the current study is the miR-146a-mediated suppression of COX-2 in lung cancer cells, as we have previously shown [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that the concept of “constitutive” and “inducible” isoforms has been challenged by growing evidence indicating that both isoforms are present in normal tissues and can be up-regulated in various pathological conditions [21]. Both the expression and regulation of COX isoforms have been intensively investigated, and reviews about transcriptional regulatory mechanisms [22], and the regulation of gene expression at the co- or post-transcriptional level [23] have been recently published.…”
Section: Introductionmentioning
confidence: 99%